2020
DOI: 10.25181/jppt.v19i2.1420
|View full text |Cite
|
Sign up to set email alerts
|

Keberhasilan Aklimatisasi dan Pembesaran Bibit Kompot Anggrek Bulan (Phalaenopsis) Pada Beberapa Kombinasi Media Tanam

Abstract: Aklimatisasi merupakan tahap yang kritis bagi plantlet. Pada lingkungan yang baru plantlet dapat mengalami cekaman lingkungan. Kondisi lingkungan seperti media yang tidak mendukung pada tahap aklimatisasi dapat menyebabkan kematian plantlet.  Penelitian ini bertujuan:  1)  Mendapatkan kombinasi  media yang paling baik bagi keberhasilan aklimatisasi plantlet anggrek Phalaenopsis; 2)Mengetahui apakah terdapat interaksi antara media bagian bawah dengan atas pot; 3) Mendapatkan kombinasi media yang paling baik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
2
0
0
2
Order By: Relevance
“…Meanwhile, [6] stated that the medium combined with coconut husk produced the best leaf length up to 10 weeks after acclimatization on Dendrobium Hybrid orchids. This was also in accordance with the research results of [29] that the use of moss medium showed the best increase in the length of the Phalaenopsis leaves.…”
Section: Leaf Length Increasesupporting
confidence: 92%
“…Meanwhile, [6] stated that the medium combined with coconut husk produced the best leaf length up to 10 weeks after acclimatization on Dendrobium Hybrid orchids. This was also in accordance with the research results of [29] that the use of moss medium showed the best increase in the length of the Phalaenopsis leaves.…”
Section: Leaf Length Increasesupporting
confidence: 92%
“…In addition, tryptone also contains nitrogen as the essential nutrient for cell division and chloroplast production in leaves (Wu et al 2014). The result of this study was in line with Ferziana and Erfa (2013) and Zeng et al (2016), that tryptone can support the growth of orchid plantlets because it contains complex nutrient needs.…”
Section: Discussionsupporting
confidence: 73%
“…Tahap aklimatisasi ini yang menjadi faktor pembatas dalam budidaya anggrek untuk mendapatkan bibit anggrek yang baik dan mampu tumbuh menjadi anggrek dewasa serta siap untuk berbunga. Tahapan ini merupakan kondisi yang kritis bagi tanaman karena kondisi lingkungan di luar berbeda jauh dengan kondisi in vitro di dalam botol kultur (Marlina, 2007;Erfa et al, 2020).…”
Section: Pendahuluanunclassified